The Differential Complement, Fc and Chemokine Receptor Expression of B Cells in IgG4-Related Pancreatobiliary Disease and Primary Sclerosing Cholangitis and Its Relevance for Targeting B Cell Pathways in Disease - Tamsin Cargill; Eleanor Barnes; Theo Rispens; Emma L. Culver (Biomedicines)
Background: Immune-mediated liver and biliary conditions, such as IgG4-related pancreatobiliary disease (IgG4-PB) and a subset of primary sclerosing cholangitis (PSC- high(h)IgG4), exhibit increased IgG4 levels in the blood. The relative expression of IgG4+ and IgG1+ B cells in the blood and the expression of complement and Fc receptors on these IgG1+ and IgG4+ B cells in IgG4-PB and PSC have not been previously described. We hypothesised that the patterns of expression of these cells and their receptors would differ, are relevant to disease pathogenesis and may represent therapeutic targets. Methods: CD19+ B cells were sorted from blood collected from patients with IgG4-PB, PSC-high(h)IgG4 and healthy volunteers. Cells were stained with fluorescent labelled antibodies specific to IgG1, IgG4, complement receptors (CR1 and CR2), Fc receptors (FcεRII and FcγRIIb) and chemokine receptors (CXCR3, CXCR4, CXCR5) and were analysed by flow cytometry. Findings: IgG4-PB, compared to healthy volunteers, showed decreased CR2 expression on IgG1+ B cells (MFI 416 (275–552) vs. 865 (515–3631), p = 0.04) and IgG4+ B cells (MFI 337 (231–353) vs. 571 (398–2521), p = 0.03). IgG4-PB, compared to healthy volunteers, showed increased FcεRII expression on IgG4+ B cells (MFI 296 (225–617) vs. 100 (92–138), p = 0.0145) and decreased FcγRIIb expression on IgG1+ B cells (134 (72–161) vs. 234 (175–291), p = 0.0262). FcγRIIb expression was also decreased in IgG1+ B cells in patients with PSC-hIgG4 compared to healthy volunteers. Conclusions: This exploratory study indicates that in IgG4-PB, B cells have decreased CR2 and FcγRIIb expression and increased FcεRII expression, suggesting altered sensitivity to complement, IgG-mediated inhibition and sensitisation by IgE, which may promote the relative expansion of IgG4+ B cells in this disease.